Avaliação da capacidade da nova linhagem de células dendríticas AP284 responder a diferentes agonistas de TLRs e de induzir uma resposta Th17 - Oliveira, Pollyana Guimarães de (2018)
Dendritic cells (DCs) are antigen presenting cells (APCs) that belongs a diversify group of cells, being still the main cells that can presents the antigen and activate T lymphocytes by inducing different kinds of cytokine production, which can influence the development of different profiles of lymphocytes. The production of IL-12p70 leads to the Th1 profile differentiation, furthermore the IL-23 production can be important for the establishment and maintenance of Th17 profile. Thus, IL-12 and IL-23 play an important role in the induction or establishment of the adaptive immune response. The aim of the study was characterize the DC AP284 cell line by checking its surface markers, TLRs expression and capacity of response to different TLRs agonists. Besides of that, the production of IL-12p40, IL-12p70, IL-23 and the ability to induce Th1 or Th17 profile were evaluated. AP284 cells have expressed surface molecules compatible with DCs including class II MHC, CD11c and 33D1. After stimulation using different TLRs agonists these cells produced higher amounts of de IL-12p40 and IL-23, but no IL-12p70 production was observed. The IFN-γ addition was not able to induce IL-12p70 production, instead of that an inhibition of the IL-12p40 and IL-23 production were observed. The results have also shown that AP284 cell line is related with the Th17 profile because higher amounts of IL-12p40 and IL-23, but not IL-12p70 were observed, besides of that the results showed an increase in IL-17 levels produced by mice lymph node cells after immunization with Freund’s adjuvant and BCG. Thus, AP284 cells can be important to study the mechanisms of induction and regulation related with the production of IL-12p40 and IL-23 working as a possible tool to study the establishment and maintenance of Th17 cells profile. Moreover, AP284 cells have some similar characteristics among the other immortalized murine DCs, but the AP284 line produces a much higher amount of IL-12p40 than all described cells and is also differentiated among them by the production of IL-23.